A biomonitoring study: trace metals in seagrass, algae and molluscs in a marine reference ecosystem (Southern Tyrrhenian Sea). (16th March 2007) - Conti, Marcelo Enrique; Iacobucci, Marta; Cecchetti, Gaetano
Marine organisms were tested as possible biomonitors of heavy metal contamination in Ustica (island of the Southern Tyrrhenian Sea). The concentrations of Cd, Cr, Cu, Pb and Zn were measured in the phanerogam Posidonia oceanica L. Delile, the two brown algae Padina pavonica (L.) Thivy and Cystoseira sp., and the two gastropod molluscs Monodonta turbinata Born and Patella caerulea L. collected at five coastal stations on the island of Ustica. The biomonitors examined showed a high ability to accumulate metals, with concentration factors higher than 10³, with respect to the concentration (soluble fraction) in marine waters. The data from this study were also compared with those previously obtained from uncontaminated sites in the Sicilian sea (Favignana island, Italy) and those obtained from the area of the Gulf of Gaeta (Tyrrhenian Sea, central Italy). Results clearly show the diversity between these three marine ecosystems.